Preserved efficacy of lyophilized SARS-CoV-2 mRNA vaccine incorporating novel ionizable lipids after one year at 25 °C - Elena Mata; Esther Broset; Carlos Matute; Andrei Stoian; Susana Adame; Teresa Alejo; Alexandre López; Beatriz Andrés; Juan Heredero; Diego de Miguel; Javier Giménez-Warren; Verónica Lampaya; et al. (npj Vaccines)
Abstract mRNA vaccines have shown great efficacy against SARS-CoV-2, yet challenges remain in optimizing vaccine components to achieve enhanced immune response and vaccine stability. In this study, we developed CPVax-CoV, a new lyophilized mRNA vaccine that features novel thiolactone-based ionizable lipids and newly designed untranslated regions (UTRs) for enhanced expression. Incorporation of these optimized components into our vaccine candidate CPVax-CoV significantly improved immune responses in mice compared to commercially available mRNA vaccines. Moreover, lyophilized CPVax-CoV has proven to be thermostable, maintaining its biological activity for up to one year at 4 °C and 25 °C after lyophilization, overcoming the cold-chain limitations of current mRNA vaccines. This vaccine demonstrates protective efficacy against ancestral SARS-CoV-2 and the Omicron XBB variant, offering a scalable solution for global distribution and pandemic preparedness. These findings underscore the potential of this platform for future next-generation mRNA vaccine development.